Prospecção de novos peptídeos com ação leishmanicida por dinâmica molecular - Guerra, Mirian Elisa Rodrigues [UNESP] (2014)
Leishmaniasis is considered one among 14 neglected diseases according to the World Health Organization, affecting about 500 million people that live in tropical and subtropical areas. The disease is caused by the infection of the host by a protozoan of the Leishmania family, and could be cutaneous, mucocutaneous or visceral. The current forms of treatment involve pentavalent antimonial drugs and others as amphotericin B; however, both cause serious side effects and some studies suggest that the parasite has already shown resistance. In this work, we investigate antimicrobial peptides with known leishmanicidal activity seeking structural parameters that could be correlated to their effectiveness against Leishmania. Seven peptides were chosen, five extracted from amphibian skins and secretions: Bombinin H2 and H4 from Bombina variegata, Temporin A and B from Rana temporaria, and Phylloseptin-1 from Phyllomedusa azurea. In addition, two peptides Decoralin with and without an amidated C-terminal, the natural form being the carboxylated, and occurring in the venom of the solitary wasp Ouremenes decoratus. The structural parameters of selected peptides were investigated by Molecular Dynamics, in a box containing the solvent TFE/water at 30/70 (v:v) concentration. Some features were found that may be related to the greater efficiency of these peptides. They include the length and stability of the α-helix, the volume of the peptides, the amphipathicity, and solvation of the backbone and terminals. Based on these features, 13 new peptides were designed to reproduce and enhance the structural features of those peptides with increased biological efficiency. The new peptides were studied by Molecular Dynamics following the same procedures used for the reference peptides. Among these new peptides some show optimized structural characteristics and will have their leishmanicidal activity determined